Family Business Corporate Governance: A Case Study of PT. Puco - Anita Maharani; Galih Rakadya (LLDIKTI Wilayah 1 Sumatera Utara, 2022)
This study is about the family business and its relation to governance in the family business, namely at PT. Puco. PT. Puco is a valve control system manufacturer in Indonesia. This research aims to identify the picture of governance in PT. Puco recommends key factors determining the success of governance at PT. Puco and create an ideal governance concept for PT. Puco. The research method used is qualitative research with data collection methods using interviews, Analytical Hierarchy Process, and the Soft System Methodology approach. The results of the research on governance description is PT. Puco has implemented governance following the ISO 9001:2015 standard but needs improvement. The research results on the key factors determining the success of governance at PT. Puco. The results propose governance model for PT. Puco consists of family and business circles. Proposed changes to resolve the problem need to be taken as an action to improve the situation.